2020
DOI: 10.1002/app.48966
|View full text |Cite
|
Sign up to set email alerts
|

The influence of processing conditions on the mechanical properties of poly(aryl‐ether‐ketone)/polybenzimidazole blends

Abstract: Interest in developing high-performance blends for niche applications has grown significantly in efforts to meet everincreasing harsh environment demands. In this work, four model poly(aryl-ether-ketone)/polybenzimidazole (PAEK/PBI) blends were chosen to study the influence of premixing methods, processing, and matrix polymers, on their mechanical properties. Among the model poly(ether ether ketone) (PEEK) and PBI blends, mechanical properties are greatly enhanced by melt premixing. The molding process mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Such studies have also shown the great influence that the polymer interphase can play in the overall mechanical properties. Jiang, Z. et al proved recently, by PeakForce quantitative nanomechanical mapping (AFM PF‐QNM) measurements, how the processing conditions of an immiscible PEEK/PBI blend affect the Young's modulus across the interphase and ultimately the fracture toughness of the blend 20 . The same technique has also proven to be successful for the detection of an enhanced interphase modulus in poly vinyl alcohol/nanodiameter 21 …”
Section: Introductionmentioning
confidence: 99%
“…Such studies have also shown the great influence that the polymer interphase can play in the overall mechanical properties. Jiang, Z. et al proved recently, by PeakForce quantitative nanomechanical mapping (AFM PF‐QNM) measurements, how the processing conditions of an immiscible PEEK/PBI blend affect the Young's modulus across the interphase and ultimately the fracture toughness of the blend 20 . The same technique has also proven to be successful for the detection of an enhanced interphase modulus in poly vinyl alcohol/nanodiameter 21 …”
Section: Introductionmentioning
confidence: 99%
“…Specimens (about 5 mg) were cut from regions away from the surface of the bulk samples. A typical three‐scan characterization was conducted under N 2 purge protection (50 mL min −1 ): (i) heating from 100 to 400 °C with a rate of 20 °C min −1 , (ii) cooling from 400 to 100 °C with a rate of 20 °C min −1 after being isothermally equilibrated at 400 °C for 10 min, which was shown to be adequate to remove thermal history effect, 17 and (iii) heating from 100 to 400 °C with a rate of 20 °C min −1 after being isothermally treated at 100 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…18 Under hot-wet condition, absorption of such a substantial amount of mobile water molecules in PBI phase would weaken the PBI phase, reducing its glass transition temperature (T g ) and increasing chain mobility. 19 Considering the intermixing of PEEK and PBI chains at their interface, 1 PEEK polymer chains at the interface would also be mobilized to some extent by its surroundings. Since the PEEK and PBI blend is at 50:50 wt% ratio, the interfacial region would strongly influence their stress relaxation behavior.…”
Section: Stress Relaxation Behaviorsmentioning
confidence: 99%
“…For example, blends of PEEK with polybenzimidazole (PBI) to combine the processability of PEEK and superior thermal mechanical properties of PBI. 1 However, PBI absorbs substantial amounts of water (>10 wt% at room temperature) which limits its applications in harsh aqueous environments. 2,3 Yuan et al, studied the hotwet environment resistance of PEEK composites reinforced by different types of fibers.…”
Section: Introductionmentioning
confidence: 99%